Fabrication of nickel oxide/copper cobaltite/graphene quantum dot conductive ink as an electrode material for selective electrochemical detection of epinephrine - Uruc, Selen; Gorduk, Ozge; Sahin, Yucel (ELSEVIER SCIENCE SA, 2025)
Wearable sensors and flexible electrodes are key components of point-of-care systems, facilitating enhanced accessibility and personalization in health monitoring. These technologies permit individuals to oversee their health status and enable healthcare professionals to remotely and in real time monitor patients' health status more effectively. In this study, paper-based flexible screen-printed electrodes were constructed for the electrochemical determination of epinephrine (EP), which is crucial in the diagnosis of various diseases, with high selectivity and low detection limits. In a novel approach, nickel oxide (NiO), graphene quantum dots (GQD), and copper cobaltite (CuCo2O4) were employed in conjunctions for the first time in the development of conductive ink. The large surface area and high electrical conductivity of GQD, when combined with the electrocatalytic properties of NiO and CuCo2O4, resulted in the creation of a more efficient electroactive environment for electrochemical EP determination. The differential pulse voltammetry technique enabled the attainment of a limit of detection (LOD) of 11.66 nM within the 500-10 mu M and 2-0.02 mu M linear ranges. The reduction peak current of EP was examined throughout the analysis to eliminate the effects of possible interference species that may be present in real samples. Furthermore, the stable structures of GQDs and copper cobaltite enhanced the long-term performance of the sensors, and the combination of these materials increased the reproducibility and reliability of the sensors. Subsequently, the efficacy of the sensor was evaluated using real samples, specifically artificial sweat, and urine. The developed NiO/CuCo2O4/GQD/G/SPE sensor demonstrated satisfactory recovery values, with 94.5-110.5 %.
Keywords: Epinephrine; Conductive ink; Flexible electrode; Sensor; Graphene quantum dots; SUPERCAPACITOR ELECTRODE; SENSITIVE DETERMINATION; OXIDE; NANOCOMPOSITES; NOREPINEPHRINE; CHROMATOGRAPHY; NANOPARTICLES; PERFORMANCE; DOPAMINE; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering